On a Human Scale. Drawing and Proportion of the Vitruvian Figure (diségno, 2020)
Among the images that describe the proportions of the human body, Leonardo da Vinci’s one is certainly the most effective, despite the fact that the iconic drawing does not faithfully follow the measurements indicated by Vitruvius.This research concerned the geometric analysis of the interpretations of the Vitruvian man proposed in the Renaissance editions of De Architectura, carried out after the aniconic editio princeps by Sulpicio da Veroli. Giovanni Battista da Sangallo drew the Vitruvian figure directly on his Sulpician copy, very similar to the images by Albrecht Dürer in The Symmetry of the Human Bodies [Dürer 1591]. Fra Giocondo proposes in 1511 two engravings of homo ad quadratum and ad circulum in the first Latin illustrated edition of De Architectura, while the man by Cesare Cesariano, author of the first version in vernacular of 1521, has a deformed body extension to adapt a geometric grid. Francesco di Giorgio Martini and Giacomo Andrea da Ferrara also propose significant versions believed to be the origin of Leonardo’s figuration due to the friendship that bound them.The man inscribed in the circle and square in the partial translation of Francesco di Giorgio’s De Architectura anticipates the da Vinci’s solution although it does not have explicit metric references, while the drawing by Giacomo Andrea da Ferrara reproduces a figure similar to Leonardo’s one. The comparison between the measures expressed by Vitruvius to proportion the man and the various graphic descriptions allows us to understand the complex story of the exegesis of the Roman treatise.
Keywords: geometry; drawing; measure; proportion; Vitruvian man